2021
DOI: 10.1017/ice.2021.416
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient antimicrobial stewardship programs in pediatric institutions in 2020: Status, needs, barriers

Abstract: Objective: To assess current resources, interventions, and obstacles of pediatric outpatient antimicrobial stewardship programs (ASP). Design: Cross-sectional study. Setting: Institutions from the Sharing Antimicrobial Reports for Pediatric Stewardship OutPatient collaborative (SHARPS-OP). Participants: Antimicrobial stewardship leaders from the above institutions. Methods: An investigator-developed survey was deployed online in Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Despite limited resources, many programs are also expanding ASPs to the outpatient setting. 16 Physician and pharmacist support for ASP overall has increased, but the majority of ASPs still report lack of time as a barrier to implementation of a successful ASP. 7 Our ASP consists of a large multidisciplinary team with organized efforts for project sharing and time management, yet team members still report challenges due to time constraints and competing priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited resources, many programs are also expanding ASPs to the outpatient setting. 16 Physician and pharmacist support for ASP overall has increased, but the majority of ASPs still report lack of time as a barrier to implementation of a successful ASP. 7 Our ASP consists of a large multidisciplinary team with organized efforts for project sharing and time management, yet team members still report challenges due to time constraints and competing priorities.…”
Section: Discussionmentioning
confidence: 99%
“…An ASP APP could fill critical roles in expanding an ASPs’ reach, particularly in outpatient and emergency department settings that remain areas of need. 46 , 47 These practice settings employ APPs at a higher rate than inpatient settings, and APPs could provide a critical perspective on intervention development and implementation. 2 While there have not been published studies on the financial benefits of ASP utilization of APPs, APPs may help expand the pool of available stewards at a lower FTE rate than physicians or pharmacists, which may benefit smaller ASPs where the financial resources can be limited.…”
Section: Our Thoughts On Effective App Engagement By Antimicrobial St...mentioning
confidence: 99%
“…We also found that the incorrect prescription of antibiotics in one of the largest children's referral hospitals in Iran had a high prevalence, which shows the urgent need to review the therapeutic and educational methods. El Feghaly et al emphasized that very few specialized children's treatment centers have dedicated standard antibiotic prescription patterns for hospitalized patients to promote treatment efforts, and this issue requires the implementation of appropriate plans by managers (24).…”
Section: Onsare Et Al Concluded That the Prevalence Of Antibiotic Pre...mentioning
confidence: 99%